Development of a framework for disassemblability design optimization for sustainable manufacturing - Raja Ghazilla, R.A.; Taha, Z. (2009)
Sustainable Product development is seen as an inevitable solution in protecting the environment. Among the important strategy in sustainable product development is through product recovery by closing the loop. Product recovery enables the reuse of depleting source of virgin material as well as avoiding the accumulation of solid waste. Maintenance can be also considered as a strategy towards sustainable product by prolonging product life time. The success of product recovery and maintenance is highly dependant on the time and cost efficiencies of the disassembly process. This paper reviews the various methods used to evaluate disassemblability. The development of the methods and its application are reviewed to provide an understanding of any missing links that have hampered the wider implementation of disassemblability design evaluations. The paper then proposes a disassemblability optimization model that can provide the missing link between design and disassembly